Remaja yang terinfeksi HIV/AIDS di Indonesia (Analisis Data Publikasi SDKI 2017) - Sapti Ayubbana; Ludiana Ludiana; Nury Luthfiyatil Fitri; Senja Atika Sari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Acquired Immune Deficiency Syndrome (AIDS) is a collection of symptoms due to a decrease in the immune system. HIV/AIDS can lower a person's immune system and make a person susceptible to serious infections. Globally, HIV/AIDS is still a public health problem. Based on the data, there are many people living with HIV whose status is still infected with HIV but have not yet entered the AIDS stage. A person's infected status can only be known through laboratory tests and can be transmitted to other people. HIV/AID does not only affect adults but can also affect infants, children and adolescents. New HIV infection among adolescents (15 – 19 years) is a problem in all regionsPurpose: To identify adolescents infected with HIV/AIDS in Indonesia based on the 2017 IDHS Publication Data Analysis related to demographic factorsMethod: Quantitative research using the Cross-Sectional method using secondary data from 2017 Indonesian Demographic and Health Survey (IDHS), conducted in December 2019-May 2020 with a sample of all adolescents aged 15-19 years, with a single status of 445. Analysis using the Chi-Square test using SPSS version 21.Results: The results showed that there was a significant relationship between the area of residence (p-value 0.00) and economic status (p-value 0.00) on know how become infected of HIV/AIDS.Conclusion: There is a relationship between the area of residence and economic status on knowledge. So that there is a need for a strategy approach and modification of the media for disseminating information on HIV/AIDS to Indonesian adolescents as an effort to reduce the incidence of HIV/AIDS in Indonesia.Keywords: Infected; HIV/AIDS; AdolescentsPendahuluan : Acquired Immune Deficiency Syndrome (AIDS) merupakan kumpulan gejala akibat penurunan sistem imun . HIV/AIDS dapat menurunkan daya tahan tubuh seseorang dan membuat seseorang mudah terinfeksi yang serius. Secara global HIV/AIDS masih menjadi permasalahan kesehatan masyarakat. Berdasarkan data terdapat banyak odha yang statusnya masih terinfeksi HIV namun belum masuk pada stadium AIDS. Seseorang berstatus terinfeksi hanya bisa diketahui melalui pemeriksaan laboratorium dan dapat menularkan kepada orang lain. HIV/AID tidak hanya mengenai orang dewasa tetapi dapat juga pada bayi, anak-anak maupun remaja. Infeksi HIV baru di kalangan remaja ( 15 – 19 tahun) merupakan masalah di semua wilayahTujuan : Untuk mengidentifikasi remaja yang terinfeksi HIV/AIDS di Indonesia berdasarkan Analisis Data Publikasi SDKI 2017 yang berhubungan dengan faktor demografiMetode : Penelitian kuantitatif dengan metode Cross Sectional menggunakan data sekunder survey Demografi dan Kesehatan Indonesia (SDKI) 2017, dilakuakan pada bulan Desember 2019-Mei 2020 dengan Sampel seluruh remaja usia 15–19 tahun, status lajang sebanyak 445. Analisa mengunakan uji Chi-Square dengan menggunakan SPSS versi 21.Hasil : Hasil penelitian menunjukkan adanya hubungan yang signifikan antara wilayah tempat tinggal ( p-value 0,00) , status ekonomi ( p-value 0,00) terhadap tahu bagaimana menjadi terinfeksi HIV/AIDS.Simpulan : Terdapat hubungan wilayah tempat tinggal dan status ekonomi terhadap terinfeksi. Sehingga perlu adanya strategi pendekatan dan modifikasi media penyebaran informasi HIV/AIDS pada remaja Indonesia sebagai upaya menurunkan angka kejadian HIV/AIDS Remaja di Indonesia.